Zaproszenie do teorii aktora-sieci – ontologia relacyjna a archeologia - Jakub Mugaj (Przegląd Archeologiczny)
Actor-Network Theory and the related ontological turn is one of the most important paradigmatic changes in contemporary social sciences. In Polish archaeological discourse Actor-Network Theory is not widely discussed. The paper presents the basic assumptions of the theory focusing on its potential for the conceptualization of archaeological sources and the relationship between humans and the environment.